Gender and occupational wage gaps in Romania: From planned equality to market inequality? - Daniela Andrén; Thomas Andrén (IZA Journal of European Labor Studies, 2015)
In Romania, the communist regime promoted an official policy of gender equality for more than 40 years, providing equal access to education and employment and restricting pay differentiation based on gender. After its fall in December 1989, the promotion of equal opportunities and treatment for men and women did not constitute a priority for any governments of the 1990s. This paper analyzes both gender and occupational wage gaps before and during the first years of the transition to a market economy and finds that the communist institutions did succeed in eliminating the gender wage differences in female- and male-dominated occupations but not in gender-integrated occupations. During both regimes, wage differences were, in general, much higher among workers of the same gender working in different occupations than between men and women working in the same occupational group, and women experienced a larger variation in occupational wage differentials than men.
Keywords: J24; J31; J71; J78; P26; P27; 330; Romania; Transition; Female- and male-dominated occupations; Gender wage gap; Occupational wage gap